Crossing through Chueca : lesbian literary culture in queer Madrid - Robbins, Jill, 1962- (University of Minnesota Press, 2011)
In the past two decades the city of Madrid has been marked by pride, feminism, and globalization--but also by the vestiges of the machismo nurtured during the long years of the Franco dictatorship. "Crossing through Chueca" examines how lesbian literary culture fares in this mix from the end of the countercultural movement la movida madrilena in 1988 until the gay marriage march in 2005. Jill Robbins traverses the various literary spaces of the city associated with queer culture, in particular the gay barrio of Chueca, revealing how it is a product of interrelations--a site crisscros